Tingkat Keanekaragaman Echinodermata Di Perairan Wuring Kecamatan Alok Barat Kabupaten Sikka - Afdal Afdal; Yulimira Syafriati Y. M. Sani; Mariana Sada (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This study aims to identify species, diversity index, abundance index, distribution pattern and correlation of abiotic factors with diversity. Number of Echinoderms in Wuring Waters, Alok Barat District, Sikka Regency. This study used a quantitative method with data collection procedures for observation, transects and documentation. As well as in analyzing data using the Shanon-Wiener formula. Then the results obtained were 4 classes with 13 species, namely Strongylocentrotus, Tripneustes gratilla, Diadema setosum, Diadema savignyi, Echinotrix calamaris, Holothuria scabra, Linckia laevigata, Luidia foliolata, Protoreaster nodosus, Ophiactis savignyi, Amphiura sp., Ophiocoma sp., and Ophiothrix fragilis. Based on these results the Echinodermata Diversity Index in Wuring waters shows a medium category, the Abundance Index has a high value and the Morisita Index. This is influenced by several environmental factors including temperature, pH and substrate.